Cross-cultural pragmatics of refusal speech acts between Malays and Germans - Mohd Jalis, Farhana Muslim (2020)
Language speakers are oftentimes caught in situations where they are unable to meet the expectations of another speaker in a certain communication situation such as requests, invitations, offers, and suggestions even if the situation is in their language. In such situations, it is somehow inevitable for them to say “no” but they may be hesitant to do so. A refusal is a speech act that is performed to convey reluctance and unwillingness to perform or agree. Successful communication requires a speaker to not only have adequate linguistic knowledge, but also a great level of understanding of how to use the language especially concerning cultural norms and how it is used in daily communication. The mutual acceptance between speakers oftentimes calls for specific strategies. This study aims to identify the refusal strategies preferred by Malay native speakers and German native speakers in situations that prompt them to refuse in their respective mother tongue. A total of 30 native Malays and native Germans working in various professional sectors participated in this study. A Discourse Completion Test (DCT) per Beebe et al. (1990) was used to obtain the data for this study. The data gathered from the DCT was analysed and coded according to a combination of the taxonomy of refusal strategies proposed by Beebe et al. (1990) and Al-Issa (2003). The finding shows that Malay and German speakers of the same social class generally used similar strategies when performing refusals albeit with different frequencies and trends. This study also looked into the influence of social variables on the choice of refusal strategies. This study has implications on both learning and teaching German and Malay languages, especially in the field of foreign languages, as it provides explanations relating to cultural behaviour and acceptance. This study may serve as a guide for educators to educate new learners and society about the pragmatics of refusal-making and the underlying cultural reasoning for this speech act to ensure successful communication in future situations that may be encountered.